Study on Media Image Management of Large Technology Enterprise - Junming, Cui; Satchanan, Siriporn; Chantanasiri, Supattra; Kositkanin, Thananwarin (วารสารนวัตกรรมการจัดการศึกษาและการวิจัย, 2023)
The aims of this research were to (1) analyze the development status of the image of large technology enterprises under the mass media and explores the fundamental factors of media image construction of large technology enterprises. (2) find out the problems existing in the media image management process of large technology enterprises from the public relations mechanism, user communication mechanism, communication mechanism, media resources and communication content, media image identification system and other aspects. And (3) provide a reference sample for establishing a standard media image identification system for large technology enterprises. The sample was 1,500 people selected by volunteer sampling. The instrument for collecting data was questionnaires on media image of science and technology enterprises. The findings: (1) Establish a user network communication mechanism based on media image and user perceived value. (2) Innovate the new media image communication and new media communication mechanism of large technology enterprises. (3) Construct a standard media image identification system for large science and technology enterprises.